Learning results and terminal values from the players of SimCity and The Sims. Issue 2 (1st February 2017) - Lin, Yu-Ling; Lin, Hong-Wen
ABSTRACT: Most research on the topic conducted in the past did not elaborate in depth on the attributes of games that correspond to specific learning results. In this study, the means-end chain theory has been adopted as the theoretical basis to focus on the players of SimCity and The Sims (two of the most representative titles of the simulation game genre) as the subjects of the research. Through in-depth interviews conducted using the Soft Laddering approach, the study aims to examine the key attributes that would trigger learning results for players when playing games and the terminal values that the players would experience internally. The study also featured group comparison of subjects based on their gender. Results of the study showed that gamers still emphasise on the key aspects of Simulated reality and Self-created game content for simulation games. These two attributes have been found to lead to the learning results of Gain authentic experience and Cultivate imagination and creativity, ultimately leading to the terminal value of Sense of accomplishment .